ChemInform Abstract: Efficient Synthesis of Cyanohydrin Trimethylsilyl Ethers via 1, 2‐Chemoselective Cyanosilylation of Carbonyls. Issue 17 (4th April 2013) - Strappaveccia, Giacomo; Lanari, Daniela; Gelman, Dmitri; Pizzo, Ferdinando; Rosati, Ornelio; Curini, Massimo; Vaccaro, Luigi
Abstract The cyanosilylation of carbonyl compounds (I) and (IV) using TmsCN (II) and triphenylphosphine supported on polystyrene as catalyst under solvent‐free conditions is described.